An Automatic Content Generator for Mazk - Sônego, Arildo A.; Santos, Jefferson P. dos; Pozzebon, Eliane; Canal, Rafael (Anais do Workshop on Advanced Virtual Environments and Education (WAVE); 2018: Anais do I Workshop on Advanced Virtual Environments and Education, 2018)
Mazk is an intelligent tutor that aims to assist the student, with the support of the computer and using techniques of Artificial Intelligence, in the teaching-learning process. Currently, all content made available to Mazk is updated manually by the human tutor. Considering the increasing amount of educational materials available, this process often becomes tiring and time-consuming. In order to optimize this task, this paper demonstrates a proposal of automatic generation of content for Mazk.